PERANAN KEPALA MADRASAH DALAM MENINGKATKAN MOTIVASI GURU DI MTs YAPERI CIBINONG BOGOR - Al-Khatib, Ibadurrahman; Aqil Ibatulloh, Muhamad (Jurnal Ilmu Pendidikan Islam, 2025)
The quality of education is highly determined by the learning process in schools and madrasas. School principals and teachers are the main movers who play an important role in the student learning process. The leadership of madrasah principals can be an important aspect in improving the quality of education. The leadership role of the principal aims to improve teacher performance and motivation through training, awarding, and role modeling. Teachers' motivation greatly affects their performance, quality, and ability. Competent and professional school principals with a high sense of responsibility are needed to realize better programs, strategies, and policies to maintain teacher motivation and performance. However, there are still some teachers who lose motivation, caused by various factors, thus affecting their discipline and performance. Therefore, the improvement and creativity of school principals in controlling teacher enthusiasm is very necessary.